1992
DOI: 10.1515/zna-1992-1-269
|View full text |Cite
|
Sign up to set email alerts
|

Zeeman Effect of Pure NQR in a Rotating Frame (CW and Pulsed Excitation)

Abstract: The Zeeman effect in a rotating frame is considered for the case when the quadrupolar nuclear spin system is acted on by two radio-frequency fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Lifting of degeneracy is possible by application of a dc magnetic field, which should be of the order of the quadrupole coupling constants and in the range from a few kHz to MHz. Another way to form the non-degenerated states is the application of RF fields, without external magnetic field [25].…”
Section: Energy Spectrum In Rotating Reference Framementioning
confidence: 99%
See 2 more Smart Citations
“…Lifting of degeneracy is possible by application of a dc magnetic field, which should be of the order of the quadrupole coupling constants and in the range from a few kHz to MHz. Another way to form the non-degenerated states is the application of RF fields, without external magnetic field [25].…”
Section: Energy Spectrum In Rotating Reference Framementioning
confidence: 99%
“…It was shown that a nuclear spin-3/2 can be represented by a two-spin system which is described using the Pauli spin-1/2 matrices 2 × 2 [12][13][14]. It means that a single spin greater than 1 2 is isomorphic to a system consisting of several coupled spins of 1/ 2 [14,15,25]. For example, in [15] the multiple-quantum spin dynamics in systems with spin 1 was studied using the fictitious spins of 1/2, forming the SU(3) group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the vicinity of the resonance, we use the approach developed in [12,13], which is based on the unitary transformation defined by the operator U (t) = exp(iDt) with…”
Section: Energy Spectrummentioning
confidence: 99%
“…and assimilate angles as = sin cos ; sin sin ; cos . In order to correctly taking into account the time dependence terms of the Hamiltonian it proves to be profitable to carry out the unitary transformation [11,12] …”
Section: Zeeman Effect In Rotating Framementioning
confidence: 99%